Immediately sequential bilateral cataract surgery: advantages and disadvantages. Issue 1 (January 2017) - Singh, Ranjodh; Dohlman, Thomas H.; Sun, Grace
Abstract : Purpose of review: The number of cataract surgeries performed globally will continue to rise to meet the needs of an aging population. This increased demand will require healthcare systems and providers to find new surgical efficiencies while maintaining excellent surgical outcomes. Immediately sequential bilateral cataract surgery (ISBCS) has been proposed as a solution and is increasingly being performed worldwide. The purpose of this review is to discuss the advantages and disadvantages of ISBCS. Recent findings: When appropriate patient selection occurs and guidelines are followed, ISBCS is comparable with delayed sequential bilateral cataract surgery in long-term patient satisfaction, visual acuity and complication rates. In addition, the risk of bilateral postoperative endophthalmitis and concerns of poorer refractive outcomes have not been supported by the literature. ISBCS is cost-effective for the patient, healthcare payors and society, but current reimbursement models in many countries create significant financial barriers for facilities and surgeons. Summary: As demand for cataract surgery rises worldwide, ISBCS will become increasingly important as an alternative to delayed sequential bilateral cataract surgery. Advantages include potentially decreased wait times for surgery, patient convenience and cost savings for healthcare payors. Although they are comparable in visual acuity and complication rates, hurdles that prevent wide adoption include liability concerns as ISBCS is not an established standard of care, economic constraints for facilities and surgeons and inability to fine-tune intraocular lens selection in the second eye. Given these considerations, an open discussion regarding the advantages and disadvantages of ISBCS is important for appropriate patient selection.